2011
DOI: 10.1186/1742-2094-8-47
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A (VEGF-A) and chemokine ligand-2 (CCL2) in amyotrophic lateral sclerosis (ALS) patients

Abstract: BackgroundVascular endothelial growth factor-A (VEGF-A) and chemokne ligand-2 (CCL2) levels have been examined in Amyotrophic Lateral Sclerosis (ALS) patients in Western countries. We measured these values in North Indian ALS patients, since these patients display considerably enhanced survival duration.MethodsSporadic ALS patients were included on the basis of El Escorial criteria. VEGF-A and CCL2 levels were analyzed in serum and cerebrospinal fluid (CSF) of 50 ALS patients using enzyme linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
6
32
0
Order By: Relevance
“…Neurotrophic factors may improve cellular function and increase neuronal metabolism, which can even lead to restoration of synaptic connections by growth of new axons. VEGF, a kind of neurotrophic factor, has been suggested to restore neuronal function, improve behavioral deficits and prolong the survival in several trails [20][21][22]. In our study, both the CSF and serum VEGF levels were significantly increased in ALS patients than those in controls, consistent with the existing reports [22].…”
Section: Elevated Vegf Level In Csf and Serum Of Patients With Alssupporting
confidence: 94%
See 3 more Smart Citations
“…Neurotrophic factors may improve cellular function and increase neuronal metabolism, which can even lead to restoration of synaptic connections by growth of new axons. VEGF, a kind of neurotrophic factor, has been suggested to restore neuronal function, improve behavioral deficits and prolong the survival in several trails [20][21][22]. In our study, both the CSF and serum VEGF levels were significantly increased in ALS patients than those in controls, consistent with the existing reports [22].…”
Section: Elevated Vegf Level In Csf and Serum Of Patients With Alssupporting
confidence: 94%
“…In our study, both the CSF and serum VEGF levels were significantly increased in ALS patients than those in controls, consistent with the existing reports [22]. It has been observed that elevated levels of VEGF in CSF, serum, and peripheral blood mononuclear cells may account for substantially prolonged life span of Indian ALS patients as compared to their Western counterparts [22][23][24]. Surprisingly, longer survival is shown in Indian ALS patients after onset (~9 year) of ALS [25,26].…”
Section: Elevated Vegf Level In Csf and Serum Of Patients With Alssupporting
confidence: 93%
See 2 more Smart Citations
“…Elevated CCL2 protein and mRNA have already been observed in serum and spinal cord autopsy of ALS patients [15]. Likewise, increased serum VEGFA was observed previously [16,17]. Demographic studies have shown that current smokers are at 1.4 to 3-fold increased risk of ALS development as compared to never smokers [18,19], although association of alcohol with development of ALS is still under question.…”
Section: Discussionmentioning
confidence: 82%